Enterocutaneous fistula: a rare complication following total abdominal hysterectomy (Journal of Kathmandu Medical College, 2014)
Postoperative enterocutaneous fistula can occur after any gastrointestinal surgery. It is however uncommon following gynaecologic procedures. Although adjacent organ fistulae such as the rectovaginal and vesico-vaginal fistulae could be seen after hysterectomy, enterocutaneous fistulae are rarely encountered. We report a case of enterocutaneous fistula on twenty second post-operative day following total abdominal hysterectomy with bilateral salphingo-oopherectomywith partial omentectomy. The patient was managed conservatively which resulted in spontaneous closure of the fistula.  DOI: http://dx.doi.org/10.3126/jkmc.v2i4.11791Journal of Kathmandu Medical CollegeVol. 2, No. 4, Issue 6, Oct.-Dec., 2013Page : 205-207